2022
DOI: 10.3389/fnbeh.2022.801825
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Dorsal Vagal Complex in Alcohol-Related Behaviors

Abstract: The neurobiological mechanisms that regulate the development and maintenance of alcohol use disorder (AUD) are complex and involve a wide variety of within and between systems neuroadaptations. While classic reward, preoccupation, and withdrawal neurocircuits have been heavily studied in terms of AUD, viable treatment targets from this established literature have not proven clinically effective as of yet. Therefore, examination of additional neurocircuitries not classically studied in the context of AUD may pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 258 publications
(307 reference statements)
0
2
0
Order By: Relevance
“…The neurobiological background of AUD affects many neurotransmitters, including peptides, that modulate brain connections in various regions. This review focuses on NT, but it is essential to consider the participation of NT in a broader context, contemplating the action of other neurotransmitters [106].…”
Section: Nt and Alcoholmentioning
confidence: 99%
“…The neurobiological background of AUD affects many neurotransmitters, including peptides, that modulate brain connections in various regions. This review focuses on NT, but it is essential to consider the participation of NT in a broader context, contemplating the action of other neurotransmitters [106].…”
Section: Nt and Alcoholmentioning
confidence: 99%
“…The DVC, which retains traumatic memories (Kolacz and Porges, 2018 ; Kolacz et al, 2019 ), contains the NTS, the DMNX, and area postrema. It has been shown that the NTS was able to project to the PVN (that is downstream to NREM-1-like EMDR SEMs-activated VLPO area) and to the NAc (Keller et al, 2022 ). As mentioned before, NAc is also able to project to the parabrachial nucleus that, in turn, projects to the NTS (Lazarus et al, 2012 ).…”
Section: Possible Neural Mechanisms Of Action Of the Emdr And Polyvag...mentioning
confidence: 99%